SISTEM AKSES SEJARAH PENYAKIT PASIEN YANG BERORIENTASI OBJEK UNTUK IMPLEMENTASI SISTEM INFORMASI KESEHATAN ( STUDI KASUS RS. KHUSUS JANTUNG SUMBAR) - Turaina, Rifa (STKIP PGRI Sumatera Barat, 2015)
The study is to analyze and modeling which oriented to objects by use of the language uml ( modelling ) for the access to the history of a patient, because there is no access to the history of a patient at an online now.Using a technique permodelan design or oriented toward the inside the system will provide kemudahkan in accessing the history of a patient and architectural design software and hardware.The prototype of these application system designed the internet duplicated at a later then performed on functionality